HUBUNGAN TINGKAT PEMAHAMAN KRIMINOLOGI DASAR DENGAN PEMBENTUKAN KARAKTER PATUH HUKUM PADA SISWA SEKOLAH DASAR (STUDI DI SD NEGERI CINTARESMI) - Ardelia Lananda; Kuswandi (LPPM Universitas Doktor Husni Ingratubun Papua, 2025)
Early childhood legal education plays a crucial role in shaping students' character to adhere to norms and laws. Basic criminological understanding is a form of legal education that needs to be implemented in elementary school students to instill the ability to recognize right and wrong behavior in social life. The purpose of this study is to examine and analyze the significant relationship between the level of basic criminological understanding and the formation of law-abiding character in elementary school students at Cintaresmi State Elementary School, as well as to measure the contribution of the level of basic criminological understanding to the formation of law-abiding character in elementary school students at Cintaresmi State Elementary School. The research method used is a quantitative method with an associative approach. Data were obtained through questionnaires that have been tested for validity and reliability, with sample determination using the Slovin formula. Data analysis was carried out using the Statistical Package for the Social Sciences (SPSS) application. The results of the study indicate a strong, positive, and significant relationship between the level of basic criminological understanding and the formation of law-abiding character in elementary school students. The correlation coefficient value shows a linear and significant relationship, while the results of the determination test show that understanding basic criminology makes a significant contribution to the formation of law-abiding character, so that the higher the level of students' understanding of basic criminology, the better the law-abiding character that is formed.